2018
DOI: 10.15761/cdm.1000169
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure: A challenging syndrome for health care professionals

Abstract: Research and evidence-based practice in heart failure (HF) have well been developed the latest years helping health professionals to cope with multiple care needs of patients with HF. The current review presents an overview of the challenging issues of health professionals who care for patients with HF. The review was based on the relevant databases of PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Cochrane Library (reviews and clinical trials). Mortality and impaired quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Heart failure (HF) is an important healthcare problem, and is associated with high morbidity and mortality rates [1]. Patients experiencing HF frequently have poor health related quality of life (HR-QoL), even when treated with modern evidence-based therapies [2,3]; such as HF management programs, new pharmacotherapy approaches such as ACE-inhibitors and b-blockers, sacubitril/valsartran, and a comprehensive approach to patient care. HF often exists with other chronic diseases, especially in older patients, resulting in complex co-morbidity conditions [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart failure (HF) is an important healthcare problem, and is associated with high morbidity and mortality rates [1]. Patients experiencing HF frequently have poor health related quality of life (HR-QoL), even when treated with modern evidence-based therapies [2,3]; such as HF management programs, new pharmacotherapy approaches such as ACE-inhibitors and b-blockers, sacubitril/valsartran, and a comprehensive approach to patient care. HF often exists with other chronic diseases, especially in older patients, resulting in complex co-morbidity conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…HF affects 6-10% of the population aged 65 years old and over in the US, estimations have indicated with will increase to 25% of the population by 2030 [5][6][7]. It is also associated with high health care costs and reduced patient HR-QoL [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Current search yielded 987 articles. Finally, eight articles were used for the current systematic review 7, 12,24,27,28,29,30,31 . The study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…12 Discussions regarding ceilings of care or withdrawal of treatment should take into account the HF patients’ current physiological status and pre-existing quality of life, any formally enacted advance directives or statements, and their personal wishes and values, including an exploration of their cultural norms and spiritual beliefs. 13 , 14 Unfortunately, as a consequence of the inordinate surge in demand for intensive care unit (ICU) beds for those requiring invasive ventilation, at times professionals have been compelled to make decisions on ICU access in the moment, based predominantly on the ethical concept of distributive justice, prioritizing allocation of this constrained resource to those considered most likely to survive. 15 , 16 An arbitrary assumption that HF patients exhibit a higher mortality risk, irrespective of their status on the disease trajectory, which renders them ineligible for this support, should be avoided.…”
Section: Communication Supportive and Palliative Carementioning
confidence: 99%